Methacrylated gelatin and mature adipocytes are promising components for adipose tissue engineering. (January 2016) - Huber, Birgit; Borchers, Kirsten; Tovar, Günter EM; Kluger, Petra J
In vitro engineering of autologous fatty tissue constructs is still a major challenge for the treatment of congenital deformities, tumor resections or high-graded burns. In this study, we evaluated the suitability of photo-crosslinkable methacrylated gelatin (GM) and mature adipocytes as components for the composition of three-dimensional fatty tissue constructs. Cytocompatibility evaluations of the GM and the photoinitiator Lithium phenyl-2, 4, 6-trimethylbenzoylphosphinate (LAP) showed no cytotoxicity in the relevant range of concentrations. Matrix stiffness of cell-laden hydrogels was adjusted to native fatty tissue by tuning the degree of crosslinking and was shown to be comparable to that of native fatty tissue. Mature adipocytes were then cultured for 14 days within the GM resulting in a fatty tissue construct loaded with viable cells expressing cell markers perilipin A and laminin. This work demonstrates that mature adipocytes are a highly valuable cell source for the composition of fatty tissue equivalents in vitro. Photo-crosslinkable methacrylated gelatin is an excellent tissue scaffold and a promising bioink for new printing techniques due to its biocompatibility and tunable properties.